Digest - Athlete experiences returning to sport after pregnancy - Caron, J.; Crozier, A.; Ede, A.; Hoffman, M.; Lee, S.; Leisterer, S.; Locke, S.; McEwan, D.; Mellano, K.; Pila, E.; Stork, M (Journal of Sport & Exercise Psychology, 2023)
In recent years, there has been a call for systemic changes to better support athletes both during pregnancy and when returning to play after giving birth. The extensive training demands and travel of elite sport present unique challenges during motherhood, yet there have not been many research studies that examine the barriers and needs of athlete mothers. Therefore, the purpose of this qualitative study was to examine the experiences of elite athletes after they returned to competition postchildbirth.